Questioning Our Questions: A Constructivist Technique for Clinical Supervision. Issue 1 (2nd January 2016) - Neimeyer, Robert A.; Woodward, Matthew; Pickover, Alison; Smigelsky, Melissa
Abstract : Consistent themes in the constructivist supervision of counseling and psychotherapy include the fostering of supervisee reflexivity, perspective taking, and capacity to generate alternative conceptualizations and interventions. In keeping with these objectives, we describe a technique for deepening therapists' reflection on their interchanges with clients through "questioning their questions" and the clients' responses to them. We further illustrate the procedure in the supervision of a therapist in training who (a) analyzed in writing a series of six question-and-answer cycles pertaining to a client, (b) considered the larger implications of the interaction for the therapeutic relationship with this client, (c) received supervisory feedback on his journaling, and (d) offered a final reflexive comment on the procedure. We conclude with a few thoughts about variations on the technique to enhance its relevance in different supervisory settings.